Evaluation of Various Maintenance Strategies for Reliability Assessment of Thermal Power Plants - Sima Zarei; Peiman Ghaedi-Kajuei (Institute of Advanced Engineering and Science, 2017)
In recent years, the world has had a phenomenal economic growth due to the acquisition of innovative technologies and globalization. In the meantime, electrical power plants are regarded as a fundamental element in industrial and production, and any deficiency in supplying may lead to significant financial detriment. Regard to the deep dependency of modern lifestyle to electricity, providing a high-quality and reliable electricity for consumers has taken on paramount importance. The reliability of a power plant depends on the configuration of elements and the reliability of each utility. The reliability, continuous service, flexibility in operation, simplicity, maintenance, development availability, meeting required standards etc. constitute the decisive factors for selection of a utility. Hence, each component of a power system must maintain the adequate level of reliability. In general, the maintenance approaches are classified into two parts: 1- The maintenance which must be carried out within determined and specified time intervals; 2- The maintenance which must be performed when required or in emergencies. To evaluate the maintenance and its effect on reliability, two types of deterministic and probabilistic approaches are presented. In this paper, a comprehensive description of both models is issued, and a detailed comparison is drawn. The results obviously show that the probabilistic models have considerable priority to deterministic models regard to their abilities for maximization of reliability or minimization of costs.